TECHNOLOGY OF DEVELOPMENT OF PHYSICAL QUALITIES OF YOUNG GYMNASTS (Academicia Globe: Inderscience Research, 2023)
In the article, the technology of developing the physical qualities of young gymnasts is highlighted on the example of the structure and distribution of training tools intended for the preliminary training group of 8-9-year-old gymnasts for the weekly microcycle.